2009
DOI: 10.1016/j.ydbio.2008.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the evolutionarily conserved cis-regulatory elements on the sox17 gene in zebrafish

Abstract: The Sox17 is an important transcription factor for endodermal cells (Danio rerio). According to the predictions of the GRNs, based on perturbation experiments and literature search, the sox17 gene is engaged with two other regulatory genes, sox32 and pou5f1. Nodal signaling operated on several endoderm-specific transcription factors to determine the endoderm specification. In addition, endoderm specification requires the Fgf and Bmp signaling pathways to be repressed in the cells which will become endoderm. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The reduction in sox17 expression after chd MO injection suggests that Chd may be upstream of sox17 in the regulatory network. This finding is consistent with the previous observations that BMP regulates endoderm formation by inhibiting endoderm markers in the ventral domain (Chan et al 2009). …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The reduction in sox17 expression after chd MO injection suggests that Chd may be upstream of sox17 in the regulatory network. This finding is consistent with the previous observations that BMP regulates endoderm formation by inhibiting endoderm markers in the ventral domain (Chan et al 2009). …”
Section: Resultssupporting
confidence: 94%
“…Bmp can repress sox17 expression (Chan et al, 2009), suggesting that Chd and Sox17 are part of an epistatic relationship in which Chd is upstream of Sox17, but such a regulatory loop would not explain the observed synergism. Thus it seems more likely that Chd and Sox17 have parallel functions in the DFC that together promote their developmental progression in the formation of the KV.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of fluorescence in situ hybridization is as described above with some modifications [14]. The RNA probe was labeled by dinitrophenyl (DNP).…”
Section: Methodsmentioning
confidence: 99%
“…We did not knock down Vegfa (a/b), Plc-ϒ, or Sox17 because in these cases early phenotypes have been reported that would be epistatic to specific later vascular defects in double loss-offunction animals. 5,41,42 We examined the overall gross phenotype and the developing vasculature of injected embryos at 48 hours post fertilization (hpf) (Figure 1). At this stage, the dorsal aorta (DA) and posterior cardinal vein (PCV) have formed distinct vessels in control embryos (Figure 1Bi-iii and Table 1) and arteriovenous separation can be clearly visualized in transverse sections through the trunk ( Figure 1C and Di-iii).…”
Section: Resultsmentioning
confidence: 99%